Pengaruh Koordinasi Kerja, Komunikasi Kerja, Penempatan Kerja, Dan Budaya Kerja Serta Semangat Kerja Terhadap Kinerja Karyawan Di Master Furniture Dan Electronik - Lubis, Mela Apriana; Pristiyono, Pristiyono; Zufrie, Zufrie (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the effect of work coordination, work communication, work placement, and work culture and morale on employee performance in Master Furniture and electronics, both partially and simultaneously.The population in this study were employees at the Master Furniture and Electronics, the research time was from January to July 2021 ,the determination of sample techniques using arikunto opinions with a total of 40 people and the analysis methods used were descriptive analysis methods, multiple linear regression analysis, and hypothesis testing.The results of partial hypothesis testing (t test) showed that work coordination (X1), work coordination (X2) and work placement (X3) had a positive and significant effect on employee performance in Master Furniture and electronics, with the value of the work coordination variable calculated at 2,813 while T table 1,689 (calculated greater than ttable). thitung work communication variable of 2,905 while T table 1,689 (thitung greater than ttable).Â  As for the work placement variable value of 2,386 While t count 1,689 (t count greater than t count). The results of simultaneous hypothesis testing (F test) showed that work coordination (X1), work communication (X2), work placement (X3), work culture (X4) and, morale (X5) had a positive and significant effect on employee performance in Master Furniture and electronics, with a ftable value of 7.141 while ftable 2.49 (ftable greater than ftable). The results of testing the coefficient of determination (R2) can be seen Adjusted R square value of 0.440 or 44% indicates that the Coordination of work, work communication, work placement, and work culture and morale simultaneously contribute to Employee Performance by 44%.